Principles of Data Structures Using C and C++ - Das, Vinu V (New Age International Ltd, 2006)
About the Book: Principles of DATA STRUCTURES using C and C++ covers all the fundamental topics to give a better understanding about the subject. The study of data structures is essential to every one who comes across with computer science. This book is written in accordance with the revised syllabus for B.Tech./B.E. (both Computer Science and Electronics branches) and MCA. students of Kerala University, MG University, Calicut University, CUSAT Cochin (deemed) University. NIT Calicut (deemed) University, Anna University, UP Technical University, Amritha Viswa (deemed) Vidyapeeth, Karunya (deemed) University and Rajasthan Vidyapeeth (deemed) University. Moreover, this book covers almost all the topics of the other Indian and International Universities where this subject is there in their undergraduate and graduate programs. All effort is made to discuss the topics in the simplest possible way without loosing its qualities. Contents: Programming Methodologies Memory Management The Stack The Queue Linked List Sorting Techniques Searching and Hashing The Trees Graphs.